Assessing the Possibility of Prosecuting the Uyghur's Genocide before the International Criminal Court - Housein Aghaei Janat Makan; Noormohammad Nowruzi (پژوهشهای حقوقی)
Genocide is one the most important International Crimes that has been adopted by the Rome 1998 Statute of the International Criminal Court and set out punishment for it in this international instrument. The crime of genocide has been conceived as mother of crimes in the doctrine. Taking place this crime in China against Uyghur Muslims has been under debate in these years. Recent report of Newlines Institute for Strategy and Policy about the Uyghur genocide allege signifies important of the issue and has attracted attention of the media and global society.This article attempts to investigate the issue through scrutinize the questions bellow: has the Actus Reus of the crime of genocide in events sequence concerned with Uyghurs proven? Does it verifyrequisite jurisdictional threshold for initiate investigations by the Prosecutor of ICC? What is the responsibility of Chinese authorities for the crimes mentioned above?In this article, intellectual effort was exerted in order to reach valid answers for the questions about the Uyghurgenocide in Xinjiang region. Based on the documents and reports of different International authorities and organizations, it was revealed the the Actus Reus of the genocide was committed.Although normative and legal possibilities in Rome Statue provides proper conditions for investigating the issue, a bulk of practical obstacles and serious impediments cause the ICC prosecutor refrain from carrying it out. This study also confirms Chinese officials’ international criminal responsibility- at the national and local level- and their mercenaries’ for the Uyghur genocide.The method used in this study is analytic-descriptive one specially analysis related international documents and reports in order to evaluate elements of the crime of genocide.